Inventory and kinematics of active and transitional rock glaciers in the Southern Alps of New Zealand from Sentinel-1 InSAR. Issue 1 (31st December 2023) - Lambiel, Christophe; Strozzi, Tazio; Paillex, Nicolas; Vivero, Sebastián; Jones, Nina
ABSTRACT: In this study, we inventoried and mapped the active and transitional rock glaciers in the central part of the Southern Alps, New Zealand, using Sentinel-1 InSAR (interferometric synthetic aperture radar) data. We used forty-three interferograms acquired between 2015 and 2019 with time intervals between six days and two years along with orthoimage analyses. A total of 123 rock glaciers were identified, of which 40 are active; that is, displaying velocities higher than 10 cm/yr. The remaining landforms are considered transitional. Among the complete sample of rock glaciers inventoried, 9 may also be interpreted as debris-covered glacierets. The number of inventoried landforms is low compared to what is observed in other similar mountain ranges, such as the European Alps. We explain this by the reduced vertical extent of the periglacial belt and the generally steep topography often not favorable for rock glacier development. Additionally, the motion rates appear relatively low. We hypothesize that a mean annual air temperature at the rock glacier locations well above 0°C is the main reason for this. These conditions may have resulted in significant ground ice melt. Rock glaciers in the Southern Alps are thus in an inactivation phase, which is expressed by typical morphologies such as stable fronts.